2020
DOI: 10.1111/ejn.14980
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine self‐administration abolishes endocannabinoid‐mediated long‐term depression of glutamatergic synapses in the ventral tegmental area

Abstract: Drugs of abuse, including cocaine, alter the mechanisms underpinning synaptic plasticity, including long-term potentiation of glutamatergic synapses in the mesolimbic system. These effects are thought to underlie addictive behaviors. In the ventral tegmental area (VTA), glutamatergic synapses also exhibit long-term depression (LTD), a type of plasticity that weakens synaptic strength. This form of synaptic plasticity is induced by low-frequency stimulation and mediated by endocannabinoid (eCB) signaling, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…While it remains to be determined, the data presented here suggest that nicotine increases eCB signaling, but that HFS is warranted to reach the threshold required for synaptic depression at excitatory terminals (Uchigashima et al, 2007;Adermark and Lovinger, 2009). Importantly, while drugs of abuse produce synaptic plasticity mechanisms in the acute phase, repeated exposure has been shown to impair eCB signaling (Blanco et al, 2016;Wang et al, 2020). This holds true not only for nicotine (Baca et al, 2013;Xia et al, 2017;Adermark et al, 2019), but also for alcohol and cocaine (Adermark et al, 2011b;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While it remains to be determined, the data presented here suggest that nicotine increases eCB signaling, but that HFS is warranted to reach the threshold required for synaptic depression at excitatory terminals (Uchigashima et al, 2007;Adermark and Lovinger, 2009). Importantly, while drugs of abuse produce synaptic plasticity mechanisms in the acute phase, repeated exposure has been shown to impair eCB signaling (Blanco et al, 2016;Wang et al, 2020). This holds true not only for nicotine (Baca et al, 2013;Xia et al, 2017;Adermark et al, 2019), but also for alcohol and cocaine (Adermark et al, 2011b;Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 68%
“…Importantly, while drugs of abuse produce synaptic plasticity mechanisms in the acute phase, repeated exposure has been shown to impair eCB signaling ( Blanco et al, 2016 ; Wang et al, 2020 ). This holds true not only for nicotine ( Baca et al, 2013 ; Xia et al, 2017 ; Adermark et al, 2019 ), but also for alcohol and cocaine ( Adermark et al, 2011b ; Wang et al, 2020 ). Especially, repeated nicotine exposure appears to impair dopamine D2R-dependent induction of LTD, rather than CB1R signaling per se ( Baca et al, 2013 ; Adermark et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…CB1R activation can reduce both inhibitory [67] and excitatory [36] drive onto VTA dopamine neurons. Notably, cocaine exposure promotes CB1R-dependent long-term depression at inhibitory synapses (iLTD) [55] while suppressing CB1R-mediated LTD at excitatory synapses [68] in the VTA, changes consistent with enhanced excitatory drive onto mesolimbic dopamine neurons. Likewise, in the NAc, CB1R activation attenuates both inhibitory [69] and excitatory [70] synaptic transmission and mediates LTD at excitatory synapses [71], including those on parvalbumin+ GABAergic interneurons [72].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of 2-AG-mediated LTD at GABAergic interneurons in the VTA resulting in disinhibition of DA neurons has been shown in animal models entailing increased DA release and projections to the NAc [37][38][39]. Preclinical findings showed that acute and repeated cocaine administration facilitates endocannabinoid-mediated LTD at GABAergic interneurons and abolishes endocannabinoid-mediated LTD at glutamatergic neurons, both resulting in increased DA release in the VTA and its projection to the NAc, contributing to the drug reinforcing effects [40][41][42]. Moreover, cocaine-induced activation of the endocannabinoid-LTD mechanism in the VTA has been recently linked to motivational behavior in rats, while the CB 1 receptor inverse agonist rimonabant was able to block reward-seeking behavior [43].…”
Section: Introductionmentioning
confidence: 97%